Counter-diffusion biofilms have lower N2O emissions than co-diffusion biofilms during simultaneous nitrification and denitrification: Insights from depth-profile analysis. (1st November 2017) - Kinh, Co Thi; Suenaga, Toshikazu; Hori, Tomoyuki; Riya, Shohei; Hosomi, Masaaki; Smets, Barth F.; Terada, Akihiko
Abstract: The goal of this study was to investigate the effectiveness of a membrane-aerated biofilm reactor (MABR), a representative of counter-current substrate diffusion geometry, in mitigating nitrous oxide (N2 O) emission. Two laboratory-scale reactors with the same dimensions but distinct biofilm geometries, i . e ., a MABR and a conventional biofilm reactor (CBR) employing co-current substrate diffusion geometry, were operated to determine depth profiles of dissolved oxygen (DO), nitrous oxide (N2 O), functional gene abundance and microbial community structure. Surficial nitrogen removal rate was slightly higher in the MABR (11.0 ± 0.80 g-N/(m 2  day) than in the CBR (9.71 ± 0.94 g-N/(m 2  day), while total organic carbon removal efficiencies were comparable (96.9 ± 1.0% for MABR and 98.0 ± 0.8% for CBR). In stark contrast, the dissolved N2 O concentration in the MABR was two orders of magnitude lower (0.011 ± 0.001 mg N2 O-N/L) than that in the CBR (1.38 ± 0.25 mg N2 O-N/L), resulting in distinct N2 O emission factors (0.0058 ± 0.0005% in the MABR vs . 0.72 ± 0.13% in the CBR). Analysis on local net N2 O production and consumption rates unveiled that zones for N2 O production and consumption were adjacent in the MABR biofilm. Real-time quantitative PCR indicated higher abundance of denitrifying genes, especially nitrous oxide reductase ( nosZ ) genes, in the MABR versus the CBR. Analyses of the microbial community composition via 16S rRNA gene amplicon sequencing revealed the abundant presence of the genera Thauera (31.2 ± 11%), Rhizobium (10.9 ± 6.6%), Stenotrophomonas (6.8 ± 2.7%), Sphingobacteria (3.2 ± 1.1%) and Brevundimonas (2.5 ± 1.0%) as potential N2 O-reducing bacteria in the MABR. Graphical abstract: Highlights: Depth profiles of N2 O and microbial community were compared between a MABR and CBR. Dissolved N2 O level was two orders of magnitude lower in the MABR than the CBR. Zones for N2 O production and consumption were close together in the MABR biofilm. Key N2 O-reducing bacteria, which may contribute to N2 O mitigation, were identified.